2020
DOI: 10.1063/1.5110273
|View full text |Cite
|
Sign up to set email alerts
|

Review of developments on polymers’ breakdown characteristics and mechanisms on a nanosecond time scale

Abstract: The breakdown of polymer insulators at a nanosecond scale is a serious problem for high-voltage devices and pulsed power systems. This paper reviews recent developments in research on the mechanisms and characteristics of the breakdown of polymers at a nanosecond scale at the Northwest Institute of Nuclear Technology. An improved avalanche breakdown model is proposed, and a formula for the strength of the electric breakdown (EBD) is formulated based on it. The formative time lag of the avalanche breakdown mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 80 publications
0
5
0
1
Order By: Relevance
“…But, this theme is not very simple to challenge because the experiments must be carried out for the polymer samples subjected to a high voltage. Different from the case of the application of a low electric field, which causes a slight change of the electron distribution in a molecule or an aggregation of molecules and the dielectric behavior can be deduced as well known, the experiment under the application of middle or high electric field, which may give us information about the changes in the electric dipole orientation, the chain conformation, the aggregation structure of the chains, and even the higher-order structure composed of the crystalline and amorphous regions, is difficult to perform for the crystalline polymer substances because of an easy occurrence of the dielectric breakdown. , The experimental reports have been quite limited even when we search the literature carefully.…”
Section: Introductionmentioning
confidence: 99%
“…But, this theme is not very simple to challenge because the experiments must be carried out for the polymer samples subjected to a high voltage. Different from the case of the application of a low electric field, which causes a slight change of the electron distribution in a molecule or an aggregation of molecules and the dielectric behavior can be deduced as well known, the experiment under the application of middle or high electric field, which may give us information about the changes in the electric dipole orientation, the chain conformation, the aggregation structure of the chains, and even the higher-order structure composed of the crystalline and amorphous regions, is difficult to perform for the crystalline polymer substances because of an easy occurrence of the dielectric breakdown. , The experimental reports have been quite limited even when we search the literature carefully.…”
Section: Introductionmentioning
confidence: 99%
“…When a high voltage was applied, the electric field is enough to accelerate the electrons to the ionization energy of the gas, and the ionized electrons would produce more electrons. As a result, increasingly more free electrons resulted in avalanche breakdown, 33,34 as shown in Figure 11B. This hypothesis was indirectly verified by the breakdown strength and the corresponding morphologies of breakdown sites in Figure 11C−E.…”
Section: ■ Results and Discussionmentioning
confidence: 58%
“…28 Regarding the influence of film thickness h on dielectric strength, it has been generally observed that inorganic dielectrics generally follow an inverse power-law dependence of dielectric strength on the film thickness, which is justified by the increased uniformity in thinner films and the presence of fewer defects. 29,30 However, for polymer films, the dielectric strength vs h relationship is not fully understood. 29 It has been shown that the dielectric strength of polymers such as poly(tetrafluoroethylene), poly(methyl methacrylate), polyethylene, etc.…”
Section: Significancementioning
confidence: 99%